Design and Build a Water and Electric Power Management System at Public Toilet Using Microcontroller-Based Hybrid Solar Cell - Ilham Jody Bimantara; Farida Arinie Soelistianto; Mochammad Junus (Jurnal Jaringan Telekomunikasi, 2022)
The need for public facilities in densely populated areas is an important matter. One of the needs for public facilities is a public toilet or commonly called MCK. However, the MCK facilities do not yet have management of charging water and electricity. One way to overcome this problem is to use a system that is able to manage water filling and electrical power in the MCK. The problem of insufficient power can be overcome by applying Solar Cell using a Hybrid system so that the existing power becomes more efficient. This study uses a water management system in the toilet bowl using ultrasonic sensors and solenoid valves. The duration of using MCK is known from the PIR sensor. The power management itself uses a hybrid solar cell system where the resources used are batteries and PLN. Then the sensor reading data is sent to firebase and displayed on the website. Based on the test, it was found that the performance of the solar cell during testing on Saturday 10 July 2021 to Monday 12 July 2021 produced an average power of 20.28Watt and the average intensity of sunlight was 680062.32lx. The power used by the load for 3 days is 0.81 kWh. The average usage on the 3 days of the trial was 9.72 Min. Quality of Service testing on a 3-day trial system obtained an average delay of 0.9637308s and packet loss of 2.2%.